FACTORS AFFECTING TRUST ON PURCHASE DECISIONS THROUGH E-MARKETPLACE - Fadhilah Fadhilah; Farah Putri Wenang L; Lina Affifatusholihah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to explain the effect of customer reviews and prices on purchasing decisions through trust, and to examine the effect of trust on purchasing decisions on e-marketplace users in Indonesia. Data was collected using a questionnaire survey of 185 active e-marketplace buyers in Indonesia. The analysis used to prove the hypothesis in this study is Structural Equation Modeling (SEM) based on components or variants known as Partial Least Square (PLS) with Smartpls 3.0 application. The results of this study indicate that trust has a positive and significant influence on purchasing decisions. While customer reviews and prices are factors that affect the trust. Where customer reviews have the greatest influence in influencing trust in purchasing decisions through e-marketplaces in Indonesia. This study offers several implications from the research results.